An Expeditious Synthesis of 1-Thiotrehalose - Tardieu, Damien; Céspedes Dávila, Maria F.; Hazelard, Damien; Compain, Philippe (Synthesis, 2018)
A two-step synthesis of 1-thiotrehalose is reported. In the key TMSOTf-mediated double thioglycosylation step, the tri-O-benzyl 1,6-anhydro-D-glucose reactant behaves both as a glycosyl donor and a glycosyl acceptor precursor. In this highly convergent process, two carbon-sulfur bonds are created at the anomeric positions with a high level of stereocontrol.
Keywords: glycomimetics; thio-sugars; anhydro sugars; domino reaction; ring-opening